Pemberdayaan Ekonomi Kelompok Penerima Manfaat Program Keluarga Harapan Melalui Kelompok Usaha Bersama (KUBE) di Kecamatan Laweyan Kota Surakarta - Pramudya, Deva; Trinugraha, Yosafat Hermawawan; Astutik, Dwi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to determine the empowerment process and the impact of economic empowerment in improving welfare and changing the mindset carried out by the Family Hope Program (PKH) Beneficiary Group (KPM) through the Joint Business Group (KUBE) in Laweyan District, Surakarta City. The type of research used is a descriptive research method with a qualitative approach. Data sources in this study were obtained from observation, interviews, and documentation. Sampling using purposive sampling. The empowerment carried out by Jajar Cemerlang and Kerten Berkah kube is in terms of managing e-stalls which are used as distribution points for disbursement of basic food aid. KUBE is an empowerment carried out in groups and under the supervision of PKH assistants in their respective regions. In the run, KUBE can improve the welfare both in terms of economic and social of its members. In Laweyan sub-district the running . In Laweyan District, the empowerment process is still limited when the schedule for food disbursement alone has not been developed through KUBE. However, when empowerment is carried out, every KUBE member can increase their income so that their daily needs can be fulfilled properly. In addition, the existence of KUBE can change the mindset of the community to no longer expect assistance from the government because the results obtained through KUBE are greater than the government assistance obtained.